ANALISA MASALAH HOLE CLEANING PADA EXTENDED REACH DRILLING SUMUR X-11 LAPANGAN Y - Widradjat Aboekasan; Gatari Dewanti (PETRO:Jurnal Ilmiah Teknik Perminyakan, 2017)
The drilling operation is an operation which is very important in the process of exploration and exploitation of oil and gas. Drilling is an important step in the exploration of oil and gas. Drilling aims for oil and gas inside the reservoir can be produced to the surface. The method itself is more advanced starts from vertical drilling, directional drilling to horizontal drilling. In an effort to acquire oil and gas need for innovations in order to optimize the recovery of oil and gas. One innovation that can optimize the acquisition of oil and natural gas are Extended Reach Drilling. Extended Reach Drilling (ERD) is part of a growing directional drilling method because it is supported by tools and a new method in the world of drilling. What differentiate ERD with conventional directional drilling method is a horizontal displacement distance its much larger.This study was conducted to evaluate the execution of ERD in the "X-11" wells "Y" field which is in the region of PT. Pertamina Hulu Energi ONWJ. By using the software WellPlanTM, which focuses on route 12-¼" evaluation results are  obtained  to  reduce  the  hole  cleaning  problems  using  drilling  mud  fluid  Low pH Desco +  3%  KCL which  has  a  value of  plastic  viscosity  (PV)  of 16 cp and yield point (YP) of  22 lbs/100 ft². To help reduce the accumulation of cuttings bed then added the use of tools Heavy Weight and Cuttings Bed Impeller. The results of the flow rate value obtained from the  calculation  of  software  for 1157,1 gpm based on the value of ROP (trial and error) that is incorporated by 115 ft/hr and the value of the pump rate (trial and error) at 1050 gpm. Based on the flow rate, ROP and pump rate the importance of the size of the cuttings bed height of 0,9 inches. This result can be considered quite good, because the standard of Pertamina Hulu Energi ONWJ is <1.